Zambia : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2017)
This Selected Issues paper assesses the sustainability of Zambia's current fiscal policies and public debt. Large fiscal imbalances and rapid increase in government debt since 2011 have raised concern about the sustainability of fiscal policies in Zambia. Fueled by the rapid exchange rate depreciation in 2014-15 and the heavy reliance on external sources to finance the growing fiscal imbalances, public external debt doubled in 2015 compared with 2014. The institutional framework for the budget process and the Medium-Term Expenditure Framework need to be strengthened. Poor commitment controls, which led to significant accumulation of payment arrears, need to be addressed. A sound Medium-Term Debt Management Strategy is required to reduce public sector debt vulnerability.